Coelomocytes: Biology and Possible Immune Functions in Invertebrates with Special Remarks on Nematodes. (30th December 2008) - Tahseen, Qudsia
Abstract : All metazoans are exposed to a wide range of microbes and have evolved complex immune defenses used to repel infectious agents. Coelomocytes play a key role in the defense reactions of most invertebrates. They are involved in important immune functions, such as phagocytosis, encapsulation, graft rejection, and inflammation, as well as the synthesis and secretion of several humoral factors especially in annelids and echinoderms. Coelomocytes in nematodes are variable in shapes from round, ovoid, cuboidal, and spindle-shaped to stellate or branched cells that are found usually at fixed positions in the pseudocoelom. Their number usually varies from 2 to 6. The model nematode, C. elegans lacks an adaptive immune system and the coelomocytes are capable of endocytosis, but their involvement in phagocytosis of bacteria seems unlikely. The aim of this review is to evaluate current knowledge on coelomocytes of invertebrates with special reference to nematodes. The morphology and structure of these coelomocytes are discussed along with their origin. Their relative positions and diversity in different nematode groups have also been discussed and illustrated.